MRI findings for diagnosis of postoperative foreign body granulomas versus recurrent tumours in patients of brain tumour surgery. Issue 4 (April 2021) - Lin, L.-Y.; Lin, S.-C.; Lee, H.-J.; Chen, S.-T.; Wu, H.-M.; Chen, Y.-W.; Chen, H.-H.; Luo, C.-B.; Guo, W.-Y.; Chang, F.-C.
Abstract : AIM: To evaluate the postoperative magnetic resonance imaging (MRI) findings of intracranial foreign body granulomas (FBGs) and true recurrent tumours (RTs) and thus lead to a basis for management decision-making. MATERIALS AND METHODS: Twenty-two patients with previous brain tumour surgery were diagnosed clinically with RT and underwent surgery. Re-operative pathology revealed FBG in eight patients and RT in 14 patients. MRI findings before the initial operation were compared to those before the re-operation. RESULTS: Features of FBGs versus RTs on MRI were as follows: (1) mean lesion size: 1.3 ± 0.7 (0.5–2.6) versus 3.2 ± 1.7 (1.1–6.3) cm ( p =0.001, odds ratio [OR] = 4.18); (2) hypointensity on T2-weighted imaging (WI): 6/8 (75%) versus 0/14 (0%; p <0.001, OR=75.4); (3) non-restricted diffusion on diffusion-WI (DWI): 6/8 (75%) versus 2/14 (14.3%; p =0.008, OR=18); and (4) "ring and bubble" appearance on contrast-enhanced T1WI: 7/8 (87.5%) versus 2/14 (14.3%; p =0.001, OR=42). In comparison with their original tumours, the FBGs in the FBG group showed significantly lower T2 signal intensity, lower signal on DWI, and more cases of non-restricted diffusion on DWI ( p =0.04, 0.04, 0.04, respectively). CONCLUSION: On brain MRI, FBGs can be differentiated from RTs by their relatively smaller size, hypointensity on T2WI, lack of restricted diffusion on DWI, and "ring and bubble" appearance on contrast-enhanced T1WI. Comparing the MRI findings of the focal lesion in the tumour bed with those of the original tumour is suggested to enhance diagnostic confidence. Highlights: Foreign body granulomas are small, low signal on T2WI and no restricted diffusion. "Ring and bubble" sign is an important clue to diagnose foreign body granulomas. Always compare surgical bed lesion with original tumor.